Pathophysiological Mechanisms of Sino-Atrial Dysfunction and Ventricular Conduction Disease Associated with SCN5A Deficiency: Insights from Mouse Models - Huang, Christopher L.; Lei, Lily; Matthews, Gareth; Zhang, Yanmin; Lei, Ming (Frontiers in Physiology, 2012)
Genetically modified mice provide a number of models for studying cardiac channelopathies related to cardiac Na+ channel (SCN5A) abnormalities. We review key pathophysiological features in these murine models that may underlie clinical features observed in sinus node dysfunction and progressive cardiac conduction disease, thereby providing insights into their pathophysiological mechanisms. We describe loss of Na+ channel function and fibrotic changes associated with both loss and gain-of-function Na+ channel mutations. Recent reports further relate the progressive fibrotic changes to upregulation of TGF-β1 production and the transcription factors, Atf3, a stress-inducible gene, and Egr1, to the presence of heterozygous Scn5a inactivation. Both changes are thus directly implicated in the clinically observed disruptions in sino-atrial node pacemaker function, and sino-atrial and ventricular conduction, and their progression with age. Murine systems with genetic modifications in Scn5a thus prove a useful tool to address questions concerning roles of genetic and environmental modifiers on human SCN5A disease phenotypes.